Increasing Emergency Department Patient Navigation And Buprenorphine Use: A Model For Low-Barrier Treatment - Samuels, Elizabeth A; Rosen, Allison D; Abusaa, Sarah; Dekker, Annette M; Schriger, David L; Shoptaw, Steven J; Kalmin, Mariah M; Lin, Chunqing; Clayton, Serena; Windels, Sarah; Keating, Elizabeth; Cisneros, Sherrie; et al. (Health affairs (Millwood, Va.), 2025)
Emergency departments (EDs) in the US treat large numbers of people with opioid use disorder (OUD), but most health systems do not equip EDs to provide OUD care. CA Bridge has supported the implementation of low-threshold, ED-initiated medications for OUD bundled with harm reduction and patient navigation in more than 80 percent of California EDs. Using grant reporting and California controlled substances prescribing data, we assessed CA Bridge implementation from July 2022 through December 2023, as well as 2022 California statewide ED buprenorphine prescribing. There were 165,671 patient navigator encounters and 44,996 instances of buprenorphine treatment at CA Bridge hospitals; patient navigator and buprenorphine treatment rates at public hospitals were more than 50 percent higher than at private hospitals. In 2022, across the entire state, 1,737 California emergency clinicians wrote 6,382 buprenorphine prescriptions; 36 percent of the people who were given those prescriptions received a subsequent buprenorphine prescription within forty days. Our findings suggest that EDs can reach large numbers of people with OUD, and buprenorphine uptake is high.